Moving My Brain to Canada: Motherhood and International Mobility as an Academic Career Requirement - Pasche Guignard, Florence (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
This article highlights the challenges encountered by mothers in academe who face the demand of international mobility as a career requirement. In order to call attention to some of the policies and strategies that best empower mothers who move, I use qualitative and quantitative studies that document the different implications of academic mobility policies for men and women and their “gendering and stratifying effects on academic careers” (Leemann and Boes 213) in conversation with some of the insights I gained through my personal experience as a mother and as a postdoctoral fellow, funded by the Swiss National Science Foundation, conducting independent research in Canada. While I locate the ideal, readily mobile and unencumbered young Swiss researcher within cultural expectations that consider mothers as primary or sole caregivers of children, I question the persistent rhetoric of sacrifice both in the maternal and in the professional academic domains. I also call attention to the tendency to silence personal experience and circumstances in most discourses promoting academic mobility to early career researchers.